In Terms of Linguistic And Programming Importance of the E-Dictionary In Ogahi's Works - Raximbayev Musobek Komiljon o‘g‘li- (Research Parks Publishers, 2023)
Digital or electronic dictionaries are software tools that contribute significantly to the advancement of linguistics. Using natural language to process (NLP) software while developing an electronic dictionary of Ogahi’s works. When developing NLP-based software, programming languages are critical. One of the most crucial issues is establishing an electronic dictionary of Ogahi's works using Python, an NLP-based computer language.